2012
DOI: 10.1155/2012/493109
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Cigarettes and Smokeless Tobacco in Minnesota

Abstract: Cigarette smokers are being encouraged to use smokeless tobacco (SLT) in locations where smoking is banned. We examined state-wide data from Minnesota to measure changes over time in the use of SLT and concurrent use of cigarettes and SLT. The Minnesota Adult Tobacco Survey was conducted four times between 1999 and 2010 and has provided state-wide estimates of cigarette smoking, SLT use and concurrent use of SLT by smokers. The prevalence of SLT was essentially unchanged through 2007, then increased significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Nationally, there is increasing concern over concurrent dual- and multi-product tobacco use. Research using Minnesota statewide data found the proportion of cigarettes smokers reporting ST use increased between 2007 and 2010 [18]. It has been suggested that the increase in ST use among smokers may be due to wide implementation of in-home and public smoking bans nationwide and the tobacco industry marketing of ST as a substitute for cigarettes when smoking is not permitted [48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nationally, there is increasing concern over concurrent dual- and multi-product tobacco use. Research using Minnesota statewide data found the proportion of cigarettes smokers reporting ST use increased between 2007 and 2010 [18]. It has been suggested that the increase in ST use among smokers may be due to wide implementation of in-home and public smoking bans nationwide and the tobacco industry marketing of ST as a substitute for cigarettes when smoking is not permitted [48].…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the lower likelihood of women being dual cigarette and ST users than exclusive ST users and the higher likelihood of women being dual cigarette and ST users when compared to exclusive smokers. Research has demonstrated that dual- and multi-product tobacco users experience lower cessation rates [17,18], possibly due to greater cotinine and dependence levels [50]. On average, AN smokers living in Bristol Bay smoke about half as many cigarettes (7.8) per day [42] as US smokers (14.2) [51], but demonstrate similar plasma cotinine levels (170 ng/mL and 200 ng/mL, respectively), suggesting altered nicotine metabolism [49,52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smokeless tobacco is being marketed as a way to use tobacco in smoke-free environments such as on airplanes, in restaurants, and at work places. 3, 4 Smokeless tobacco is a risk factor of cancer of the oral tissues and pharynx, oral soft tissue lesions (such as leukoplakia), periodontal disease, gingivitis, caries, halitosis, tooth loss, tooth stains, and nicotine addiction. 5 Smokeless tobacco has also been associated with low birth weight babies 5 and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%